2018
DOI: 10.22219/jrak.v8i2.32
|View full text |Cite
|
Sign up to set email alerts
|

Do Earnings Management Able to Reduce Stickiness Cost Levels?

Abstract: The purpose of this research is to determine the occurence of stickiness cost in SG&A (Selling, General and Administration) cost and to see whether the stickiness cost degree can be derive through earning management. Multiple linear regression using regression model from Anderson et al. and Farzaneh et al. are carried out to analyze the data. The results of this research show that SG&A cost is sticky, because it increased by 0.908% at 1% increase in sales but decreased by 0.016% at 1% decrease in sales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Every 1% increase in net sales will increase SG&A costs by 1,077, whereas every 1% decrease in net sales will decrease SG&A costs by (1,077-1,484) -0.407%. Thus, it can be concluded that hypothesis one is accepted because the percentage increase is greater than the percentage decrease, or in other words, SG&A costs for consumer industry sector companies listed on the IDX in 2016-2018 are sticky, along with research conducted by Martania [3], Xue and Hong [6] and Wahyuningtyas and Nugrahanti [12] indication of stickiness cost behavior at SG&A costs. Based on table 2, the value of the coefficient of β1, β2 and β3 coefficient determine the truth of the hypothesis of the two proposed in this study.…”
Section: Results and Analysismentioning
confidence: 95%
See 3 more Smart Citations
“…Every 1% increase in net sales will increase SG&A costs by 1,077, whereas every 1% decrease in net sales will decrease SG&A costs by (1,077-1,484) -0.407%. Thus, it can be concluded that hypothesis one is accepted because the percentage increase is greater than the percentage decrease, or in other words, SG&A costs for consumer industry sector companies listed on the IDX in 2016-2018 are sticky, along with research conducted by Martania [3], Xue and Hong [6] and Wahyuningtyas and Nugrahanti [12] indication of stickiness cost behavior at SG&A costs. Based on table 2, the value of the coefficient of β1, β2 and β3 coefficient determine the truth of the hypothesis of the two proposed in this study.…”
Section: Results and Analysismentioning
confidence: 95%
“…The behavior of cost changes implemented in cost accounting is actually asymmetrical (proportional) characterized by the rigidity of costs when a decrease in activity occurs, contrary to the theory of the nature of activity volume and cost changes which are said to be symmetrical. The existence of this imbalance is assumed to occur due to a decrease in costs that are lower than the volume of activity that comes from a decrease in the volume of activity, a situation like this is called stickiness costs [3].…”
Section: A Stickiness Costmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research also find the determinant of stickiness cost (Pichetkun and Panmanee, 2012). Some researches find the earnings management gave effect on stickiness cost (Rezaei and Barandagh, 2016;Martani, Eltivia and Setiawan, 2018). Bosch & Blandon (2011) found that size of the companies give effect on stickiness cost.…”
Section: Introductionmentioning
confidence: 99%